Composição mineral da cana-de-açúcar in natura hidrolisada com cal virgem (CaO) - Domingues, Felipe Nogueira; Oliveira, Mauro Dal Secco De [UNESP]; Mota, Diego Azevedo; Oliveira, Raimundo Parente De; Santos, Juliana Dos; Miranda, Augusto Sousa; Godoy, Bruno Spacek (UFBA - Universidade Federal da Bahia, 2014)
The aim of this study was to evaluate the mineral composition of in natura sugarcane hydrolyzed with increasing doses of quicklime and different periods of exposure to air. The levels of quicklime (CaO) used were 0.0 (control); 0.5; 1.0; 1.5 to 2.0% based on natural matter of cane and the time of exposure to air at 0; 24; 48; 72 and 96 hours. The mineral composition was assessed through the concentrations of calcium (Ca), phosphorus (P), potassium (K), magnesium (Mg), zinc (Zn), copper (Cu), manganese (Mn), chromium (Cr), lead (Pb) and cadmium (Cd). We used a completely randomized design. Data were analyzed using analysis of variance with repeated measures for comparison of means by Tukey test at 5% probability was used. The Ca concentration changes (P<0,05) caused a modification of the Ca:P ratio in the hydrolyzed sugarcane that reached 36.46:1 at the highest dose of lime (2.0%). The levels of P, K, Mg, Zn and Cu decreased with increasing levels of quicklime (P<0,05). Regarding to the period of exposure to air, there was an increase in the concentration of K, Mg, and Mn (P<0,05). The treatment of sugarcane with microprocessed quicklime (CaO) increases the Ca content of the forage. Pb is present in the quicklime but in a concentration well below the toxic concentration for ruminants.

Objetivou-se avaliar a composição mineral da cana-de-açúcar in natura hidrolisada com doses crescentes de cal virgem e diferentes tempos de exposição ao ar. As doses de cal virgem (CaO) utilizadas foram 0,0 (controle); 0,5; 1,0; 1,5 e 2,0% com base na matéria natural da cana e os tempos de exposição ao ar 0; 24; 48; 72 e 96 horas. A composição mineral foi avaliada através das concentrações cálcio (Ca), fósforo (P), potássio (K), magnésio (Mg); zinco (Zn), cobre (Cu), manganês (Mn), cromo (Cr), chumbo (Pb) e cádmio (Cd). Utilizou-se o delineamento inteiramente casualizado. Os dados foram analisados utilizando uma análise de variância com medidas repetidas, para a comparação das médias foi utilizado o teste de Tukey ao nível de 5% de probabilidade. A variação no teor de Ca (P<0,05) ocasionou alteração na relação Ca:P da cana-de-açúcar hidrolisada, chegando a relação de 36,46:1 na dose mais elevada de cal (2,0%). Os teores de P, K, Mg, Zn e Cu diminuíram com a elevação da dose de cal (P<0,05). Em relação ao fator tempo, houve um acréscimo na concentração K, Mg e Mn (P<0,05). O tratamento da cana-de-açúcar com cal virgem (CaO) microprocessada aumenta o teor de Ca do volumoso ocasionando um aumento na relação Ca:P. Há presença de Pb na cal virgem, porém abaixo da concentração tóxica para ruminantes.
Mineral composition of cane sugar in natura hydrolyzed with quicklime (CaO)
Keywords: hydrolyzing agent; macro minerals; heavy metals; micro minerals; alkali treatment; calcium oxide; agente hidrolizante; macro minerais; metais pesados; micro minerais; tratamento alcalino; óxido de cálcio